Pengaruh Disiplin Kerja, Leader Member Exchange dan Motivasi Kerja Terhadap Produktivitas Kerja Di Rumah Sakit Mitra Medika Medan - Syaputra, Afrizal; Handoko, Bagus; Pentana, Sopi (Jurnal Ekonomi Bisnis Digital, 2022)
This research is associative in nature and uses a quantitative approach. The population in this study consisted of 400 respondents, with a sample of 80 respondents determined using the Slovin formula. The respondents were employees from Mitra Medika Medan Hospital. Data was collected using questionnaires and analyzed using multiple linear regression analysis.The results showed that work discipline has a positive and significant effect on work productivity, with a contribution of 0.427. This means that work discipline plays an important role and can increase work productivity by 42.70%. Leader–member exchange also has a positive and significant effect on work productivity, with a contribution of 0.151, indicating that good leader–member relationships can improve work productivity by 15.10%.In addition, work motivation has a positive and significant effect on work productivity, with a contribution of 0.333, meaning that work motivation can enhance productivity by 33.30%.